Risk Factors of Stunting Incidence Among Children in the Working Area of Berampu Public Health Center, Berampu District, Dairi Regency, 2024 - Robert Harnat; helfi nolia (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2026)
In 2024, there are 150.2 million children under five years old suffering from stunting worldwide, with the largest contribution coming from Asia (52% of all children globally) and 43% from Africa. Stunting is a condition of growth failure in toddlers (children under five years old) caused by chronic malnutrition over a long period. This condition results in a child's height being below the age standard. Based on Length/Height-for-Age (L/A or H/A), nutritional status is categorized into very short height, short, normal, and tall. Very short and short categories are classified as stunting. Indonesia’s target for reducing stunting is 14% by 2024. The Indonesian Nutrition Status Survey (SSGI) in 2022 shows a stunting rate of 21.6%, which decreased compared to 24.4% in 2021. The prevalence of stunting in Indonesia further decreased in 2023 (21.5%) compared to 2022 (21.6%) according to data from the Indonesia Health Survey, with nine provinces, including North Sumatra Province, having stunting prevalence below 20% (18.9% in 2023). In Dairi Regency, stunting prevalence in 2022 was 28.6%, which is a reduction of 5.6% from 34.2% in 2021. Globally, 4.2 billion people live without safely managed sanitation access. The percentage of drinking water facilities meeting drinking water quality standards in Indonesia (2023) reached 72.22%, hitting the target of 72%. North Sumatra Province, however, had a lower achievement in drinking water quality monitoring in the fourth quarter of 2023 at 70.08%. The study aims to identify factors causing stunting and establish the Gerakan Desa Sehat Atasi Stunting (Deshat) in Berampu District, Dairi Regency, as an effort to accelerate stunting reduction based on Presidential Regulation No. 72/2021 and Dairi Regent Regulation No. 1/2023, conducted jointly or convergently as an integrated cross-sectoral issue with intervention activities that are both sensitive and specific, including providing and ensuring access to safe drinking water and sanitation. This research uses a beginner scheme. The method is quantitative observational analytic with a cross-sectional approach to examine the relationship between parenting patterns, hygiene, water quality test results, water treatment, and sanitation with stunting. Sampling technique: total sampling. Statistical tests used were chi-square with ɑ=0.05 and logistic regression. The research location was Berampu District with a sample of 58 stunted toddlers. The research output included scientific publications in a nationally accredited SINTA 4 journal and Intellectual Property Rights (IPR) for the Healthy Village Movement to Overcome Stunting (Deshat). The results showed a democratic parenting pattern among respondents with a p-value of (0.000) < 0.05, indicating a significant relationship where families not applying democratic parenting have an 8.5 times higher risk of having stunted children compared to those who do. Physical quality of water had a p-value of (0.001) < 0.05, showing a significant relationship between the physical quality of drinking water and stunting incidence; prevalence of stunting in children with poor physical water quality was 3.5 times higher than in children with good water quality. Water treatment results had a p-value of (0.007) < 0.05, indicating a significant relationship between water treatment and stunting incidence; prevalence of stunting among children with poor water treatment was 2.4 times higher compared to those with good water treatment.